Collaborative Learning: Perceptions of Teacher Educators - Verma, Diksha; Katoch, Kuldeep Singh (Voices of Teachers and Teacher Educators, 2024)
This study focused on collaborative learning (CL) techniques and whether and how teacher educators implement them in their teaching practices. Their general perception of the effectiveness of CL techniques, how they choose a particular technique over another, and the challenges in implementing these techniques are discussed. A questionnaire with mixed items was developed and utilized for data collection and responses from 28 teacher educators were computed using a simple percentage method for closed items and content analysis in the case of open-ended items. The study identified significant challenges in implementing collaborative learning (CL) in teacher training. This study shed light on the present practices of CL in teacher education programs and how teacher educators’ pedagogical orientation towards CL techniques is important so that our pre-service teachers can learn these from their teachers and can implement these techniques effectively in their future classes.